2012 IEEE International Geoscience and Remote Sensing Symposium 2012
DOI: 10.1109/igarss.2012.6352492
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution SAR and high-resolution optical data integration for sub-urban land-cover classification

Abstract: This study shows a comparison between pixel-based and object-based approaches in data fusion of high-resolution multispectral GeoEye-1 imagery and high-resolution COSMO-SkyMed SAR data for land-cover/land-use classification. The per-pixel method consisted of a maximum likelihood classification of fused data based on discrete wavelet transform and a classification from optical images alone. Optical and SAR data were then integrated into an object-oriented environment with the addition of texture measurements fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Due to the aforementioned issues, up to now, no standard data processing technique has been presented to detect oil slicks with optical images. This paper describes a new method for the tracking of surface oil slicks using MODIS imagery, which is based on the fluorescence/emissivity index (Gianinetto et al 2010a) and object-based image analysis OBIA (Rusmini et al 2012). Two case studies are presented: the Deepwater Horizon (DWH) and the Campos Basin (CB) oil spill accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the aforementioned issues, up to now, no standard data processing technique has been presented to detect oil slicks with optical images. This paper describes a new method for the tracking of surface oil slicks using MODIS imagery, which is based on the fluorescence/emissivity index (Gianinetto et al 2010a) and object-based image analysis OBIA (Rusmini et al 2012). Two case studies are presented: the Deepwater Horizon (DWH) and the Campos Basin (CB) oil spill accidents.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the literature considered medium-resolution data, typically Landsat-TM or SPOT for optical and RADARSAT or ERS for radar. At present, only few studies reported case histories of thematic classification involving both MS and SAR images collected with metric or submetric spatial detail [7], [8], [10], [11], [13], [30], [31]. Furthermore, most of them debated the mapping in urban areas or in natural areas and only few managed both LC/LU in the same classification workflow.…”
Section: Integration Of Cosmo-skymed and Geoeye-1 Datamentioning
confidence: 98%
“…The integration of SAR and optic imagery was found to be very useful in crop classification using various methods, such as artificial intelligence (AI) algorithms or wavelet transformation [13][14][15]. For crop monitoring, this integration was studied via two approaches.…”
Section: Introductionmentioning
confidence: 99%